K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 12 2015

\(\left(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\right)^2=\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{c^2}+2\left(\frac{a+b+c}{abc}\right)\)

\(2^2=2+2.\frac{a+b+c}{abc}\Rightarrow\frac{a+b+c}{abc}=1\Rightarrow a+b+c=abc\)

AH
Akai Haruma
Giáo viên
13 tháng 8 2018

Lời giải:

Muốn chứng minh \(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}=\frac{1}{abc}\) ta chỉ cần chỉ ra \(ab+bc+ac=1\)

Thật vậy:

\((a+b+c)^2-(a^2+b^2+c^2)=2^2-2\)

\(\Leftrightarrow a^2+b^2+c^2+2(ab+bc+ac)-(a^2+b^2+c^2)=2\)

\(\Leftrightarrow 2(ab+bc+ac)=2\Rightarrow ab+bc+ac=1\)

Do đó ta có đpcm.

25 tháng 8 2016

a) a3+b3+a2c+b2c-abc

= (a+b)(a2-ab+b2)+c(a2+b2)-abc

=(a+b) [ (a+b)2-3ab]+c.[(a+b)2-2ab]-abc

=(a+b)(a+b)2-3ab(a+b)+c(a+b)2-3abc

=(a+b)2(a+b+c)-3ab(a+b+c)

=(a+b)2.0-3ab.0

=0

b) ax+ay+2x+2y+4

=a(x+y)+2(x+y)+4

=(x+y)(a+2)+4

=(a-2)(a+2)+4

=a2-4+4

=a2

c) A=1+x+x2+...+x49=>Ax=x+x2+x3+...+x50

                                           - A=1+x+x2+...+x49

                               ---> Ax-A=x50-1

d)(a+b)(a+c)+(c+a)(c+b)

=a2+ac+ab+bc+c2+bc+ac+ab

=a2+c2+2ac+2ab+2bc

=2b2+2bc+2ac+2ab

=2b(b+c)+2a(b+c)

=2b(b+c)(b+a)